The impact of human resource management practices on employee engagement and moderating role of gender and marital status: An evidence from the Vietnamese banking industry - Bui Nhat Vuong; Suntrayuth Sid (Management Science Letters, 2020)
The aim of this research is to examine the effect of human resource management (HRM) practices on employee engagement, and the moderating roles of gender and marital status. The survey was conducted with a total of 457 frontline employees who are working in the Vi-etnamese banking industry. Partial least squares structural equation modeling (PLS-SEM) was estimated using the SmartPLS 3.0 program to examine the hypotheses. The results indicated that HRM practices and its four key dimensions (Training; Reward and recognition, Employee engagement, and Information sharing) positively impacted employee engagement. Moreover, this study provided an empirical evidence about the moderating roles of gender and marital status. It implied that male frontlines employees heightened the positive relationship between HRM practices and employee engagement, but this positive relationship was weakened by married employees. The finding also suggested that bank managers should develop a suitable HRM practices to reinforce employee engagement.